Mediating Shari’a and Religious Freedom: The Case of the So-Called False Prophet in Indonesia - Afifur Rochman (Religió: Jurnal Studi Agama-agama, 2020)
Indonesia’s religious blasphemy law has been used to restrict the religious freedom of the so-called false prophet (nabi palsu). The prominent examples are Lia Eden and Ahmad Musadeq, to name but a few. They were previously Muslim and later maintain their prophethood respectively, claiming to be the heir of preceding prophets, most notably within the Abrahamic religions. Referring to this law, both Eden and Musadeq are arrested for the charge of blasphemy against religion. This article seeks to examine the phenomenon of Indonesian prophets from the perspective of Shari’a and human rights to religious freedom in the Indonesian context. Can both Shari’a and the Human Rights accommodate the Indonesian prophethood? This article aims at reconciling the two different viewpoints in favor of the realization of justice and equality regardless of religious identity. The reconciliation I propose implies evaluating permissible restrictions of religious freedom within the Indonesian legal framework that takes religious values into consideration.